Factores económicos y financieros que inciden en el desarrollo de las pymes en el cantón Quevedo, año 2020. plan estratégico - Castro Fernández, Diana Carolina (2021)
Every globally recognized company started small. A shared key to the success of these organizations lies in their ability to see the goal and effectively plan their actions to achieve it. The bottom line from this is that whenever an initiative arises to start a business, the first thing for long-term key success is to establish a clear reason for existence (Mission), a big dream that drives the company's operations (Vision) and fundamental principles that would guide your daily decision-making (Values). Objectives and goals should be established and communicated across the team to ensure that operational and human capabilities are aligned with the strategy execution requirements. For this, an economic and financial analysis of the SMEs in the Quevedo canton and their evolution in their management structure will be carried out, using as the main source of information the surveys and interviews to be carried out with a sample of 335 owners of SMEs that work in the city. of Quevedo. The result of this information will serve to identify the strengths and weaknesses of SMEs and suggest recommendations. Finally, this study will allow the project to implement a strategic plan aimed at improving the economic situation of SMEs, seeking to achieve the proposed objectives for a solution for the benefit of all. Keywords: economic and financial factors, SMEs, development, FADO, strategic plan.